Inclusive Leadership and Quality of Work Life: Their Impact on Organizational Commitment with Job Satisfaction as a Mediator - Wildan, Muh Khaerul; Prayekti, Prayekti; Hadi, Syamsul (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Effective organizations need leaders who create inclusive and quality work environments to increase team commitment. Inclusive leadership and good quality of work life together increase satisfaction, loyalty, and organizational performance. So, this study aims to determine the effect of inclusive leadership and quality of work life on organizational commitment with job satisfaction as an intervening variable. This research uses all employees who work in the Sub-district Office Wera, with the sampling technique using the saturation method so that the number of samples from all members of the population was 96 employees. Data processing using inferential partial least square (PLS) method, variance-based SEM using Smart-PLS software version 3.2.9. The results showed that inclusive leadership was shown to have a positive effect on organizational commitment, quality of work life was not shown to have a positive effect on organizational commitment, inclusive leadership was shown to have a positive effect on job satisfaction, quality of work life was shown to have a positive effect on job satisfaction and job satisfaction was shown to have a positive effect on organizational commitment with job satisfaction proving to be an intervening relationship between inclusive leadership on organizational commitment and job satisfaction proving to be an intervening relationship between quality of work life on organizational commitment.